A case of disseminated extranodal Rosai-Dorfman disease diagnosed by skin manifestations - Shintaro Saito; Akihiko Uchiyama; Yayoi Shibusawa; Sei‐ichiro Motegi (Frontiers Media S.A., 2023)
Abstract Rosai-Dorfman disease (RDD) is a rare non‐Langerhans cell histiocytosis that was first described as sinus histiocytosis with massive lymphadenopathy by Rosai and Dorfman in 1969. While classical/nodal RDD is typical, extranodal involvement is seen in up to 43% of all cases, with 23% showing only extranodal lesions. Here, we present a case of disseminated extranodal RDD, where the initial symptoms were cutaneous manifestations.